Exploring Emirati Parental Perspectives: A Comprehensive Analysis of Attitudes Towards Counseling and Guidance Services in Private School Settings - HAJEBI, ASMA ABBAS (2024)
This study investigates Emirati parental attitudes towards counseling and guidance services in private school settings in Dubai, UAE. Motivated by the observed disconnect between Emirati parents' limited awareness and appreciation for counseling services despite the prevalence of depressive symptoms among Emirati children, the qualitative methodology employed semi-structured interviews with a sample of Emirati parents to elucidate parental perceptions and experiences regarding counseling services. Thematic analysis revealed several key findings. Firstly, ingrained gender dynamics in parenting roles were identified, with fathers often assuming the role of enforcers of discipline, while mothers were primarily tasked with academic support and day-to-day aspects of children's education. Secondly, prevalent fear and stigma surrounding counseling were highlighted, with concerns raised about potential social repercussions and damage to the family’s reputation, deeply embedded in cultural norms prioritizing maintaining familial honor and social standing. Additionally, a significant lack of knowledge and misconceptions surrounding counseling among Emirati parents emerged as a remarkable theme. Participants expressed uncertainty about the role and effectiveness of counseling services, reflecting the impact of cultural and religious norms on attitudes toward mental health services. Addressing these challenges requires culturally sensitive interventions, including education campaigns, community outreach programs, and the involvement of religious leaders to challenge misconceptions and promote a more supportive environment for seeking mental health support. Data analysis involved importing the interviews into qualitative analysis software such as ATLAS to facilitate coding and systematic organization. Through semi-structured interviews with Emirati parents, the research aimed to explore how the quality and presence of counseling services impact parental attitudes and perceptions, examining factors like awareness levels, cultural norms, and the perceived significance of emotional well-being relative to academic achievement. In conclusion, this study contributes to a deeper understanding of the cultural, social, and religious factors shaping parental attitudes toward counseling in the UAE. The findings underscore the importance of targeted interventions and collaborative efforts to address stigma, promote awareness, and integrate culturally sensitive counseling services into educational settings. Recommendations include the development of culturally sensitive counseling programs, mandatory mental health education in schools, training for educators and healthcare providers, and media literacy programs to address the impact of social media on mental health. Further research is needed to explore the effectiveness of interventions targeting parental attitudes towards counseling and their impact on children's mental health outcomes in the UAE, ultimately fostering a supportive environment for Emirati children's holistic development and well-being.